2010
DOI: 10.1177/1087054710361586
|View full text |Cite
|
Sign up to set email alerts
|

Late Adolescent and Young Adult Outcomes of Girls Diagnosed With ADHD in Childhood: An Exploratory Investigation

Abstract: Objective-The study aims to characterize the late adolescent and young adult outcomes of girls diagnosed with ADHD in childhood.Method-The study included 58 females from a larger longitudinal study of ADHD. Thirty-four (M=19.97 years old) met DSM criteria for ADHD in childhood, while the remaining 24 (M=19.83 years old) did not. Self-and parent-reports of psychopathology, delinquency, interpersonal relationships, academic achievement, job performance, and substance use were collected.Results-The findings sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
98
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 42 publications
16
98
7
1
Order By: Relevance
“…Regarding family and attachment relations, those difficulties generate higher divorce rates than the general population. Babinski et al (2011) have also demonstrated that young girls with ADHD have a tendency towards confrontational relationships with their mothers, fewer romantic relations and more depressive symptoms than control subjects. This emotional dysregulation can also lead to high-risk behaviours, possibly through poor management of emotions such as anger, especially while driving: ADHD subjects are more likely of being involved in serious accidents, speeding violations or other infractions of traffic regulations than control subjects (Chang et al, 2014;Fried et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…Regarding family and attachment relations, those difficulties generate higher divorce rates than the general population. Babinski et al (2011) have also demonstrated that young girls with ADHD have a tendency towards confrontational relationships with their mothers, fewer romantic relations and more depressive symptoms than control subjects. This emotional dysregulation can also lead to high-risk behaviours, possibly through poor management of emotions such as anger, especially while driving: ADHD subjects are more likely of being involved in serious accidents, speeding violations or other infractions of traffic regulations than control subjects (Chang et al, 2014;Fried et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…With higher base‐rate levels of emotional problems among girls in the general Swedish population 74, the associations between ADHD and internalizing/emotional problems reported here could to some extent be explained by covariation. However, higher rates of internalizing and/or emotional problems among girls with ADHD have been commonly reported in both clinical and population‐ or community‐based studies 8, 16, 19, 29, 46, 75, 76, 77, 78, 79, 80, 81. Thus, ADHD symptoms seem to contribute to the total internalizing problem load in a gender‐specific manner 61.…”
Section: Discussionmentioning
confidence: 99%
“…Because a number of large prevalence studies have suggested that the male: female ratio of the disorder may be markedly lower than once believed, especially in adulthood (e.g., DuPaul et al, 2001;Kessler et al, 2005;Ramtekkar et al, 2010;Simon et al, 2009), research on ADHD in young women presents an urgent area of need (see also Gaub & Carlson, 1997;Gershon, 2002). Overall, girls with ADHD may be at particularly high risk for negative outcomes over time (see Babinski et al, 2011;Biederman et al, 2010Biederman et al, , 2012Chronis-Tuscano et al, 2010;Dalsgaard, Mortensen, Frydenberg, & Thomsen, 2002;Hinshaw et al, 2012).…”
Section: Adhd In Femalesmentioning
confidence: 99%
“…In terms of diagnostic persistence, Babinski et al (2011) examined rates of ADHD in the female subsample of the Pittsburgh ADHD Longitudinal Study (PALS). Of the 58 female participants (34 probands, 24 controls), assessed at a mean age of 19.9 years, ADHD was found to persist in 41% (via parent-report utilizing DSM-IV criteria), compared to only 13% via selfreport.…”
Section: Adhd In Femalesmentioning
confidence: 99%